Correlations between physical and chemical defences in plants tradeoffs, syndromes, or just many different ways to skin a herbivorous cat? - Moles, Angela T (The New phytologist, 2013)
© 2013 The Authors. New Phytologist © 2013 New Phytologist Trust.